2021
DOI: 10.1016/j.jpha.2020.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shengmai Yin on the DNA methylation status of nasopharyngeal carcinoma cell and its radioresistant strains

Abstract: Shengmai Yin (SMY) is a Chinese herbal decoction that effectively alleviates the side effects of radiotherapy in various cancers and helps achieve radiotherapy's clinical efficacy. In this study, we explored the interaction mechanism among SMY, DNA methylation, and nasopharyngeal carcinoma (NPC). We identified differences in DNA methylation levels in NPC CNE-2 cells and its radioresistant cells (CNE-2R) using the methylated DNA immunoprecipitation array and found that CNE-2R cells showed genome-wide changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…However, the high expression of TNC in nasopharyngeal carcinoma (NPC) cell line CNE-2 caused by abnormal demethylation induced radioresistance. A previous study ( Liu et al, 2021 ) indicated that Shengmai Yin radiosensitized NPC radioresistance cell line by partial hypermethylation of TNC, which suggests Shengmai Yin can be used as a potential radiosensitizer or epigenetic drug for NPC. The goal of epigenetic therapy is “epigenetic reprograming” by a drug that reverses abnormal epigenetic activity in cancer cells and the critical benefit of epigenetic drugs is their innocuity.…”
Section: The Effect Of Traditional Chinese Medicine On the Regulation...mentioning
confidence: 98%
“…However, the high expression of TNC in nasopharyngeal carcinoma (NPC) cell line CNE-2 caused by abnormal demethylation induced radioresistance. A previous study ( Liu et al, 2021 ) indicated that Shengmai Yin radiosensitized NPC radioresistance cell line by partial hypermethylation of TNC, which suggests Shengmai Yin can be used as a potential radiosensitizer or epigenetic drug for NPC. The goal of epigenetic therapy is “epigenetic reprograming” by a drug that reverses abnormal epigenetic activity in cancer cells and the critical benefit of epigenetic drugs is their innocuity.…”
Section: The Effect Of Traditional Chinese Medicine On the Regulation...mentioning
confidence: 98%
“…The epigenetic regulation can regulate the expression of TAAs in different tumor cells. In clinical applications, DNA methyltransferase inhibitor (DNMTi) treatment can improve tumor immunogenicity and immune recognition by promoting the re-expression of TAAs [ 52 ]. Drugs that act on epigenetic modification enzymes have been widely used in the clinical treatment for patients with tumor ( Table 1 ) [ 53 , 54 ].…”
Section: Gene Expression Changes Caused By Epigenetic Modificationmentioning
confidence: 99%
“…Clinically, SMY is often used to supplement Qi and nourish Yin in TCM theories. Since the lack of Qi and Yin is a common phenomenon in cancer patients who receive radio or chemical therapy, the treatment of SMY in these patients has achieved well effects and has become a research hotspot [ 9 , 10 ]. Moreover, SMY was also widely applied for the interventions of various cardiovascular disorders including myocarditis [ 11 ], diabetic cardiomyopathy [ 12 ], myocardial infarction [ 13 ], myocardial ischemia-reperfusion [ 14 ], and heart failure [ 15 ].…”
Section: Introductionmentioning
confidence: 99%